Genetic deletion and pharmacological inhibition of PI3Kγ reduces neutrophilic airway inflammation and lung damage in mice with cystic fibrosis-like lung disease - Galluzzo, Maria; Zhou-Suckow, Zhe; Mall, Marcus A. (Mediators of inflammation, 2015)
Purpose. Neutrophil-dominated airway inflammation is a key feature of progressive lung damage in cystic fibrosis (CF). Thus, reducing airway inflammation is a major goal to prevent lung damage in CF. However, current anti-inflammatory drugs have shown several limits. PI3Kγ plays a pivotal role in leukocyte recruitment and activation; in the present study we determined the effects of genetic deletion and pharmacologic inhibition of PI3Kγ on airway inflammation and structural lung damage in a mouse model of CF lung disease. Methods. βENaC overexpressing mice (βENaC-Tg) were backcrossed with PI3Kγ-deficient () mice. Tissue damage was assessed by histology and morphometry and inflammatory cell number was evaluated in bronchoalveolar lavage fluid (BALF). Furthermore, we assessed the effect of a specific PI3Kγ inhibitor (AS-605240) on inflammatory cell number in BALF. Results. Genetic deletion of PI3Kγ decreased neutrophil numbers in BALF of /βENaC-Tg mice, and this was associated with reduced emphysematous changes. Treatment with the PI3Kγ inhibitor AS-605240 decreased the number of neutrophils in BALF of βENaC-Tg mice, reproducing the effect observed with genetic deletion of the enzyme. Conclusions. These results demonstrate the biological efficacy of both genetic deletion and pharmacological inhibition of PI3Kγ in reducing chronic neutrophilic inflammation in CF-like lung disease in vivo.
Gesehen am 06.08.2021